RADIOECOLOGICAL STUDIES IN URBAN SOIL OF VANADZOR (Proceedings of the YSU C: Geological and Geographical Sciences, 2021)
The work summarizes the results of radioecological studies of soils implemented in one of the largest cities of Armenia: the city of Vanadzor. Gamma spectrometric and iMatic gas-less counting systems (CANBERRA) were applied to determine the specific activities of natural radionuclides (40K, 226Ra, 232Th) and gross α/β activities, respectively. Radiological indices and excess lifetime cancer risk were calculated according to the methodology of the UN Scientific Committee on the Effects of Atomic Radiation (UNSCEAR). Statistically significant correlation was found between the activities of 232Th and 40K. The relatively high values of gross α/β activities were found in the northern and western parts of the city. In the case of natural radionuclides, the average (17.08 Bq/kg) and geochemical background (16.88 Bq/kg) of 226Ra and do not exceed the UNSCEAR value for the soil of Armenia (46 Bq/kg). The highest activities of 226Ra were found mainly in the northern part and city center. The average activity of 232Th (29.66 Bq/kg) was close to UNSCEAR average value (30 Bq/kg) and the background (37.03 Bq/kg) slightly exceeds. In most parts of the city, 232Th does not exceed the background value. For 40K the average activity (390.44 Bq/kg) was found to be higher than UNSCEAR value. The background value (469.0 Bq/kg) also exceeds the UNSCEAR average, however, the activities of all investigated radionuclides are within the ranges. 40K also does not exceed the background in most of the city. Radionuclide-associated radiological hazards, in particular, absorbed gamma dose rate, annual effective dose equivalent, radium equivalent activity, and cancer risk do not exceed the reference values.
Keywords: natural radionuclides; urban soil; cancer risk; Vanadzor